Assessing supportive needs in pregnant women with substance use, a qualitative study - S. Heidarifard, PhD; M. Khoshnamrad, PhD (AJOG Global Reports)
Pregnant women with substance use (SUD), are a vulnerable group with special reproductive health needs. The study aimed to assess the supportive needs of pregnant women with substance use. This study adopted a 3-phase qualitative methodology: (1) qualitative content analysis to identify supportive needs, (2) a 3-round Delphi process involving 20 purposively sampled experts (conducted via email over 6 months), and (3) a nominal group technique session with 10 of the original experts to prioritize critical needs. The focus was on pregnant women with substance use disorder. Five categories of needs emerged: socio-cultural support, health/financial support, consultation services, psychological needs, and access to training. Among these, education on sexual health, sexually transmitted diseases, and harm reduction principles during pregnancy scored highest (mean: 3.95). Expert consensus via the nominal group emphasized developing an educational protocol based on the Theory of Planned Behavior to address behavioral changes aligned with maternal needs. The paramount need for pregnant women with SUD is structured education on sexual health and harm reduction in pregnancy. Findings advocate for tailored, theory-based interventions to provide holistic support, potentially improving maternal and fetal outcomes.